Implementation of Counseling Services on ibunda.id Platform in Overcoming Mental Health Problems - Hasan Bastomi; Diana Fitriani; Maulida Rizqiyyatul Chusna; Safitra Salwa; Muhammad Sholeh (Pamomong: Journal of Islamic Educational Counseling, 2022)
This research aimed to reveal the implementation of the counseling service on ibunda.id platform in overcoming mental health problems. This field research used a qualitative approach with interviews, observation, and documentation techniques in collecting the data. The results showed that the main background of Ibunda.id was utilizing technology to ease anything, including counseling services. The implementation of the Ibunda.id counseling service in dealing with mental health problems was as follows: (1) Establishing a relationship with the counselees using friendly greetings, (2) Reflecting on the counselees' empathy and appreciating their courage to share their story/problems, and then finding the solutions, (3) Providing self-help psychoeducation to train their ability in solving daily problems and developing their character.